Rendering the popular as Tradition: the music of Virgilio Pirot Petcheller and the Panay Bukidnon Banda music practice in Panay Island, Philippines - Taton, Jose R. Jr. (Tanjong Malim, 2020)
Rendering the popular as Tradition: the music of Virgilio Pirot Petcheller and the Panay Bukidnon Banda music practice in Panay Island, Philippines by Taton, Jose R. Jr.